Srikandi of the Ministry of Religious Affairs: Women’s Leadership in PTKIN Confronting Patriarchal Culture - Valensius Ngardi; Ferdi Yufriadi; Sahrul Sori Alom Harahap; Tri Wibowo; Musnif Istiqomah (Modern Islamic Studies and Sharia Research, 2025)
This study investigates the role of female leaders, referred to as the "Srikandi of the Ministry of Religious Affairs," in shaping leadership practices within State Islamic Higher Education Institutions (PTKIN) in Indonesia, within the context of a patriarchal cultural framework. The research adopts a qualitative approach using a case study design, combining in-depth interviews, document analysis, and observations to capture the lived experiences and strategies employed by female leaders across several PTKIN in the country. The study finds that women leaders in PTKIN face significant structural and cultural challenges stemming from patriarchal norms, yet they actively navigate these barriers by adopting adaptive leadership styles. These women leaders skillfully balance professionalism, religious values, and gender equity in their roles. Their leadership practices reflect resilience, negotiation skills, and strategic networking, allowing them to gain legitimacy and authority within male-dominated environments. The study highlights that the presence of female leaders in PTKIN serves as a transformative force, subverting patriarchal hegemony and creating opportunities for more inclusive and egalitarian governance within Islamic higher education. By contributing to the ongoing discourse on gender and leadership in this context, the research provides new insights into how women leaders navigate cultural constraints, assert their agency, and enhance institutional performance in the face of systemic gender inequality. The study underscores the importance of fostering supportive environments that allow women to thrive in leadership roles within religious and educational institutions.